The Relationship between Athletes' Attitudes for Healthy Eating and Exercise Dependence - Guler, Hasan; Sural, Volkan; Car, Bekir; Tolukan, Ersan (Progress in Nutrition, 2021)
Study Objectives: This study aimed to evaluate athletes 'attitudes towards healthy eating and exercise dependence according to age, gender, sports experiment, branch and number of exercises per week, and to examine the relationship between athletes' attitudes towards healthy eating and exercise dependence. Methods: The universe of the study, which performed according to the relational screening model, one of the quantitative approaches, consisted of Turkish athletes in amateur sports. Besides, the sample of the study consisted of 389 athletes residing in Ankara and determined by the easily accessible sampling method. The data of the study was collected online using the Attitude Scale for Healthy Nutrition and the Exercise Dependence Scale. SPSS software was used for data analysis, independent samples t-test was used for paired comparisons, and One-way ANOVA was used for multiple comparisons. The Pearson Correlation Coefficient was used to determine the relationship between attitude towards healthy eating and exercise dependence. Results: It was determined that while gender, age, sports experience and training per week affected athletes' attitudes towards healthy eating, the branch did not have any effect. Age and weekly training were effective on exercise dependence of athletes, while gender, branch and sports experience did not have any effect. There was a significant positive correlation between athletes' attitudes towards healthy eating and their exercise dependence. Conclusion: These results showed that as exercise dependence levels increased, their attitudes towards healthy eating also increased.